Highly sensitive salinity sensing using annular one-dimensional photonic crystals - Hassan Sayed; Ashour M. Ahmed; Ali Hajjiah; M. A. Abdelkawy; Arafa H. Aly (Scientific Reports)
Abstract This study explores annular one-dimensional (1D) photonic crystals (PCs) in detail as potentially useful instruments for applications involving salinity detection. The distinctive configuration of annular 1D PCs facilitates the containment and manipulation of light within a concise and unified framework, facilitating the creation of compact and portable sensing apparatus suitable for on-site applications and real-time monitoring. Unlike conventional planar and texturing-based PC sensors, the annular configuration enhances light confinement and defect mode engineering, leading to superior sensing performance. The study describes the simulation process that uses the COMSOL Multiphysics technique and the Finite Element Method (FEM) to create annular 1D PCs, underscoring the criticality of precise management of layer thickness and uniformity. Wherein, the structure of a 1D- annular PC is created as $${(AB)}^{N}D {(AB)}^{N}$$ , since A represents Silicon dioxide ( $$Sio_{2})$$ and B signifies Titanium dioxide ( $$Tio_{2}$$ ) with material thicknesses set at 850 nm for each. D represents the central defect layer from saline water, which equals 3400 nm, and N equals 5. Hence, we achieve an exceptional sensitivity of 1910.6 nm/RIU, surpassing most reported 1D-PC salinity sensors. Also, the materials used in our design ( $$SiO_{2} and TiO_{2})$$ are highly chemically and mechanically stable which resistant to etching in the saline water. Furthermore, we discuss the feasibility of fabricating the proposed sensor using advanced nanofabrication techniques, ensuring its practical implementation in environmental and biomedical monitoring applications.